The Halsey isotherm for water contaminant adsorption is fake - Chu, Khim Hoong; Bashiri, Hadis; Hashim, Mohd Ali; Abd Shukor, Mohd Yunus; Bollinger, Jean-Claude (Elsevier, 2023)
We present a critique of the Halsey isotherm model (also known as Frenkel–Halsey–Hill), which is used by many researchers to interpret water contaminant adsorption data. We first convert the original Halsey isotherm for gasphase adsorption to a form appropriate for liquid-phase adsorption. We call this version the “genuine Halsey isotherm.” We then show that the Halsey isotherm currently used in water contaminant adsorption research bears only a partial resemblance to the genuine Halsey isotherm. As such, we label the former the “fake Halsey isotherm.” We go on to prove that the fake Halsey isotherm is mathematically equivalent to the Freundlich isotherm. Consequently, the modeling results obtained by the fake Halsey isotherm reported in numerous previously published studies have been mostly misleading. Many such reports can be found across a broad spectrum of major journals. Finally, we highlight the data-fitting attributes of the genuine Halsey isotherm. It is shown to be capable of describing adsorption isotherms having types I, II, and III curve shapes.